Genetics of Atrial Fibrilation: In Search of Novel Therapeutic Targets - Lozano-Velasco, Estefanía; Garcia-Padilla, Carlos; Aránega, Amelia E.; Franco, Diego (Cardiovascular & Haematological Disorders - Drug Targets, 2019)
Atrial fibrillation (AF) is the most frequent arrhythmogenic disease in humans, ranging from 2% in the general population and rising up to 10-12% in 80+ years. Genetic analyses of AF familiar cases have identified a series of point mutations in distinct ion channels, supporting a causative link. However, these genetic defects only explain a minority of AF patients. Genomewide association studies identified single nucleotide polymorphisms (SNPs), close to PITX2 on 4q25 chromosome, that are highly associated to AF. Subsequent GWAS studies have identified several new loci, involving additional transcription and growth factors. Furthermore, these risk 4q25 SNPs serve as surrogate biomarkers to identify AF recurrence in distinct surgical and pharmacological interventions. Experimental studies have demonstrated an intricate signalling pathway supporting a key role of the homeobox transcription factor PITX2 as a transcriptional regulator. Furthermore, cardiovascular risk factors such as hyperthyroidism, hypertension and redox homeostasis have been identified to modulate PITX2 driven gene regulatory networks. We provide herein a state-of-the-art review of the genetic bases of atrial fibrillation, our current understanding of the genetic regulatory networks involved in AF and its plausible usage for searching novel therapeutic targets.
Keywords: Atrial fibrillation